Multiple intradural spinal metastases of esthesioneuroblastoma: A case report. (August 2015) - Mohindra, Sandeep; Tripathi, Manjul; Mohindra, Satyawati; Savardekar, Amey; Radotra, Bishan D.
Abstract Spinal metastases from esthesioneuroblastoma (ENB) might have variable presentations. Discrete lesions, even when multiple, warrant radical excision, followed by radiotherapy. The authors present a case of anterior skull base ENB, metastasizing to spine at muliple levels. Clinical and radiological pictures are described with intraoperative findings.